2016
DOI: 10.1111/tid.12619
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal histoplasmosis in a patient after autologous stem cell transplant for multiple myeloma

Abstract: A 59-year-old patient with multiple myeloma on maintenance chemotherapy presented with fever, weight loss, and night sweats. An F-18 fluorodeoxyglucose (FDG) positron emission tomography (PET) computed tomography (CT) showed intra-abdominal lymphadenopathy with a mesenteric mass that led to further workup and diagnosis of histoplamosis. The patient was treated with amphotericin B and subsequently switched to itraconazole. This exemplifies the usefulness of FDG PET CT in diagnosis of infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…A PET scan demonstrated that the pulmonary nodule and an associated hilar lymph node were hypermetabolic indicative of a localized histoplasmoma with a reactive regional lymph node. Although it is not the usual standard of care, the use of PET imaging has been previously reported to assist in the diagnosis of histoplasmosis and invasive fungal infections in general [5,10,11]. Because culture and Histoplasma antigen testing were negative in our patient's case, the use of pan-fungal primers to amplify DNA from the organism for sequencing was vital in making the diagnosis.…”
Section: Discussionmentioning
confidence: 88%
“…A PET scan demonstrated that the pulmonary nodule and an associated hilar lymph node were hypermetabolic indicative of a localized histoplasmoma with a reactive regional lymph node. Although it is not the usual standard of care, the use of PET imaging has been previously reported to assist in the diagnosis of histoplasmosis and invasive fungal infections in general [5,10,11]. Because culture and Histoplasma antigen testing were negative in our patient's case, the use of pan-fungal primers to amplify DNA from the organism for sequencing was vital in making the diagnosis.…”
Section: Discussionmentioning
confidence: 88%
“…4 Gastrointestinal histoplasmosis is particularly uncommon, usually always found along with DH and mostly asymptomatic. 4,5 Inhalation of microconidia, often from a soil source, is the usual method of inoculation with Histoplasma. Once in the alveoli, Histoplasma transitions to the yeast phase and is ingested by phagocytic cells, which can then hematogenously disseminate the organism to the rest of the body and form granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated histoplasmosis (DH) is more commonly seen in immunosuppressive conditions, likely because of ineffective macrophage function 4 . Gastrointestinal histoplasmosis is particularly uncommon, usually always found along with DH and mostly asymptomatic 4,5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations